2003
DOI: 10.1002/abio.200390032
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of the Nitrate Nitrogen and Nitrogen Dioxide to Nitrous Oxides in Plants

Abstract: Tobacco and wheat are known to emit nitrous oxide (N 2 O). Provided that N 2 O is a greenhouse gas about 300 times worse than carbon dioxide in its potential for global warming, it is an intriguing and important subject, whether this activity is commonly present in other plants. In this study, 17 plant taxa that had been cultured aseptically were fed with 15 N-labelled nitrate for one week (feeding period). The plant taxa were then transferred to a medium with non-labelled nitrate in gas-sealed pots and cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 38 publications
3
57
1
Order By: Relevance
“…The correlation between N 2 O emissions from plants (N 2 O E ) and plant respiratory coefficient (R E ) in this study indicated that N 2 O emissions from plants might be associated with plant respiration. Hakata et al (2003) also found that there was more than a 58-fold variation in the 'N 2 O Emission' in the 17 plant taxa, which suggested plants N 2 O emissions might be involved with plant intrinsic physiological characteristics. On the other hand, night-time plant transpiration appears to be potentially widespread in plants.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The correlation between N 2 O emissions from plants (N 2 O E ) and plant respiratory coefficient (R E ) in this study indicated that N 2 O emissions from plants might be associated with plant respiration. Hakata et al (2003) also found that there was more than a 58-fold variation in the 'N 2 O Emission' in the 17 plant taxa, which suggested plants N 2 O emissions might be involved with plant intrinsic physiological characteristics. On the other hand, night-time plant transpiration appears to be potentially widespread in plants.…”
Section: Discussionmentioning
confidence: 86%
“…The result obtained by Smart and Bloom (2001) demonstrated that wheat leaves emit N 2 O during nitrate assimilation. A study with 17 plant taxa indicated that plant N 2 O emission was common in plant tissues (Hakata et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Second, UV-B radiation may lower plant N 2 O production. It is extensively reported that soybean crops can produce and release part of N 2 O for the physiological reaction of plant tissues (Li et al 2003;Hakata et al 2003;Rochette et al 2004). Soybean crops can produce and release part of N 2 O, which is strongly positively correlated with the content of nitrate and activity of foliar nitrate reductase (NR) (Li et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Since the early report that detached fresh soybean organs may produce N 2 O (Chen et al, 1990), a number of studies have reported N 2 O emissions from plants (e.g., Chen et al 1992Chen et al , 2002Hakata et al 2003;Huang et al 1992;Li and Chen 1993;Zhang 2001;Zhang et al 2002a, b) and have indicated a considerable contribution of plant emissions to the N 2 O release from soil-plant systems (e.g., Chen et al 2003;Pihlatie et al 2005;Smart and Bloom 2001;Xu et al 2001;Zou et al 2005). In a considerable portion of these studies, the DN method was used in GCECDs to analyze air samples collected from chamber enclosures.…”
Section: N 2 O Emission From Plantsmentioning
confidence: 99%
“…In addition, living plants also release N 2 O (e.g., Chen et al 1990;Smart and Bloom 2001). To quantify the intensities from these sources, N 2 O emission measurements from natural and managed soils, soil-plant systems (e.g., Stehfest and Bouwman 2006) and plants (e.g., Hakata et al 2003;Pihlatie et al 2005;Zou et al 2005) have been carried out worldwide. Global estimates of 1.7-4.8 and 3.3-9.0×10 12 g N 2 O-N yr −1 for agricultural terrain and soils under natural vegetation, respectively, have been given (IPCC 2007).…”
Section: Introductionmentioning
confidence: 99%